INOVASI PENDIDIKAN AGAMA ISLAM - Muhammad Nur Hadi; Syaifullah; Wiwin Fachrudin Yusuf (Fakultas Agama Islam, 2022)
This research is motivated by the current condition of Islamic religious education in Indonesia, which is still experiencing problems in various aspects and efforts to improve it have not been carried out in a basic way, seeming improvised. The government's attention to Islamic education is very small, on the other hand the government expects the people to have a socialist and religious spirit. It can be said that Islamic education in Indonesia occupies a